(untitled) (Research, Society and Development, 2024)
Background: Dopamine and dopaminergic pathways are crucial in antipsychotic treatment and the emergence of akathisia. Understanding these mechanisms is essential for effectively managing this condition. Objective: This study aims to highlight the management of akathisia in a patient with schizophrenia while underscoring the significance of dopaminergic mechanisms in treatment. Methods: Following the CARE (CAse REports) guidelines, this study presents a case report that serves as a practical representation of clinical scenarios, contextualizing theoretical concepts through real-world examples, enhancing the understanding of rare conditions and unique treatment responses. Case Report and Discussion: A 59-year-old female patient diagnosed with schizophrenia developed severe akathisia after starting risperidone. She exhibited intense restlessness and emotional distress, requiring adjustments to her treatment regimen, including the addition of propranolol, clonazepam, and phenytoin. This case illustrates the intricate relationship between dopamine dysregulation and akathisia, emphasizing the necessity for personalized treatment strategies tailored to the patient’s needs. It highlights the importance of close monitoring and flexible management in addressing adverse effects associated with antipsychotic medications. Furthermore, fostering a supportive therapeutic relationship with the mental health team and incorporating familial support significantly contributed to the patient’s overall treatment success. Conclusion: Understanding dopaminergic pathways is vital for managing akathisia and schizophrenia. This study advocates for a holistic treatment approach that integrates clinical insights with psychosocial factors to improve the patient’s quality of life and treatment adherence.